Integrated metabarcoding and culture-dependent assessments reveal Pseudomonas as dominant hyphosphere-pathobiont in Race 4 Fusarium wilt pathogen of cotton - Antony-Babu, Sanjay; Abeysinghe, Gayan; Thomas, Vanessa Elizabeth; Hockenbury, Cara; Parunandi, Shravan Sharma; Dasgupta, Amrita; Gregory, Tristan Andrew; Gabu, Amrita Sai; Ball, Haden; Chappell, Thomas M.; Shaw, Brian D.; Isakeit, Thomas; et al. (Frontiers in Microbiology, 2025)
The hyphosphere, the microhabitat surrounding fungal hyphae, hosts complex microbial interactions that can influence fungal biology, yet the microbial community in hyphospheres of pathogenic fungi are seldom characterized. In this study, we investigated the hyphosphere of Fusarium oxysporum f. sp. vasinfectum Race 4 (FOV4), a major fungal pathogen threatening cotton, to characterize its bacterial community and assess potential functional roles. An integrated approach was employed combining confocal time-lapse microscopy, 16S rRNA metabarcoding, culture-dependent bacterial isolation, whole genome sequencing, and fungal-bacterial coculture assays. Microscopy confirmed hyphosphere association, and the bacterial predisposition towards the growing hyphal tips. Metabarcoding showed a stable hyphosphere community dominated by a single Pseudomonas ASV accounting for over 95% of relative abundance, with strong negative correlations to most other taxa. To evaluate the functions, ten representative bacterial isolates were sequenced, revealing enrichment in metabolic pathways related to carbon, nitrogen, and sulfur cycling. In particular, Pseudomonas laurylsulfatiphila showed high counts of oxidoreductases and hydrolases. Coculture assays demonstrated that several bacterial isolates significantly promoted FOV4 hyphal extension, while having limited or inconsistent effects on other Fusarium strains, indicating strain-specific interactions. Together, the findings reveal a stable and functionally enriched bacterial community in the FOV4 hyphosphere, with potential implications for fungal fitness and virulence. These results support the emerging concept of a hyphosphere-pathobiome and highlight microbial associations as targets for future plant disease management strategies.